Event Synchronous Segmentation of Phonocardiogram-A New Frontier to Heart Sound Delineation - Vishwanath Madhava Shervegar (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
Background: Phonocardiography is the study of human cardiac sounds. Phonocardiograms (cardiac sounds) as they are called, represent the most vital physiological and pathological information about the human body. Objective: This paper presents an automatic method of segmentation of heart sounds using the occurrence of cardiac rhythmic events. Methods: Noisy heart sound is filtered using the 6th order Chebyshev type I low pass filter to remove the redundant noise. The Bark Spectrogram is calculated from the cardiac signal by converting the spectrogram to the Bark scale. The bark spectrogram is smoothened and the loudness index is calculated by averaging the amplitude across all frequency bands. The loudness index is smoothened and differentiated to obtain the event detection function. The smoothened event detection function gives the occurrence of the cardiac events namely the first and the second heart sounds. Result: This method is highly effective in identifying peaks S1 and S2 with a segmentation accuracy of 96.98% giving an F1 measure of 97.09%. Conclusion and significance: This method does not require the setting up of any type of noise threshold. So, it is a highly effective type of segmentation of phonocardiogram corrupted with noise. To reduce the effect of noise the noisy phonocardiogram is heavily filtered using the time-frequency block thresholding method.